Mekanisme Pengambilan Keputusan Kepala Madrasah Tsanawiyah Nurul Huda Desa Nusantara Jaya Kecamatan Keritang Kabupaten Indragiri Hilir Provinsi Riau - Asmariani, Asmariani; Sain, Moh.; Kumalasari, Nona (STAI Auliaurrasyidin Tembilahan, 2022)
Decision making is essentially a process of choosing one method or course of action from various alternatives to achieve the desired result. Important elements in the decision-making process, namely decision-making must be based on existing facts, based on management's objective considerations and assessment of the situation, based on experience and general views. This study aims to determine the decision-making mechanism of the head of Madrasah Tsanawiyah Nurul Huda Kilo Meter 5 Desa Nusantara Jaya, supporting and inhibiting factors, as well as efforts to overcome obstacles that hinder decision making. The method used in this study is qualitative with a descriptive-analytical approach, while the data collection techniques used are observation, interviews, and documentation studies.